Complications of transurethral plasmakinetic resection of prostate: a systematic review and meta-analysis - Bing-Hui LI; Shi-Di TANG; Yong-Bo WANG; Si-Yu YAN; Jia-Ao LOU; Yu-Qing DENG; Tong DENG; Ying-Hui JIN; Xiao-Dong LI; Xian-Tao ZENG (Yixue xinzhi zazhi)
Objective To evaluate complications related to transurethral plasmakinetic prostatectomy (TUPKP) in the treatment of benign prostatic hyperplasia (BPH).Methods CNKI, Wanfang database, VIP Chinese journal service platform, CBM, PubMed, Embase, Web of Science and The Cochrane Library were searched for cross-sectional studies on the incidence of complications of TUPKP in the treatment of BPH from January 1st, 2018 till to September 15th, 2020. Two researchers independently screened the literature, extracted data and evaluated the risk of bias in the included studies, the R software meta package was used for meta-analysis.Results Twenty-seven studies were finally included, reporting on 5,247 patients with 31 complications described. Meta-analysis showed that the incidence of 6-month abnormal ejaculation rate is 75.15% [95%CI (68.25%, 81.47%)]; the incidence of retrograde ejaculation is 24.77% [95%CI (0.00%, 73.81%)]; the incidence of irritating symptoms was 17.15% [95%CI (9.61%, 26.22%)]. The incidence of other complications was less than 10%, and 21 of them had an incidence of less than 3%. The incidence of transurethral resection syndrome in 15 studies was 0.Conclusion There are many types of complications after TUPKP treatment for BPH, and the incidence rate varies greatly.